Feature-based translation of CAD models with macro-parametric approach: issues of feature mapping, persistent naming, and constraint translation. Issue 5 (9th April 2020) - Safdar, Mutahar; Jauhar, Tahir Abbas; Kim, Youngki; Lee, Hanra; Noh, Chiho; Kim, Hyebin; Lee, Inhwan; Kim, Imgyu; Kwon, Soonjo; Han, Soonhung
Abstract: Feature-based translation of computer-aided design (CAD) models allows designers to preserve the modeling history as a series of modeling operations. Modeling operations or features contain information that is required to modify CAD models to create different variants. Conventional formats, including the standard for the exchange of product model data or the initial graphics exchange specification, cannot preserve design intent and only geometric models can be exchanged. As a result, it is not possible to modify these models after their exchange. Macro-parametric approach (MPA) is a method for exchanging feature-based CAD models among heterogeneous CAD systems. TransCAD, a CAD system for inter-CAD translation, is based on this approach. Translators based on MPA were implemented and tested for exchange between two commercial CAD systems. The issues found during the test rallies are reported and analyzed in this work. MPA can be further extended to remaining features and constraints for exchange between commercial CAD systems. Graphical Abstract: